Preparation method of water-based zinc ion battery negative electrode modified by super-hydrophobic anti-corrosion coating

By modifying ultra -hydrophobic anti -corrosion coating on the negative electrode of the zinc ion battery of the water system, the problem of lowering and uneven deposition of zinc electrode in the water cell battery in the water system has been solved. Essence

CN119381410APending Publication Date: 2025-01-28HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411367997.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In applications, aqueous zinc ion batteries face problems such as low redox potential, local alkaline environment formation, uneven deposition and dendrite growth, resulting in electric field imbalance, membrane penetration, internal short circuit and Coulomb efficiency, limiting their industrial applications.

Method used

Using ultra -hydrophobic anti -corrosion coating to modify the negative electrode of the zinc ion battery of the water system. The combination of hydrophobic nano -nano -nano -nano -sanxide and inorganic aluminum phosphate forms a thick coating of 2 to 3 μm. The contact of the film.

Benefits of technology

Effectively improve the shelving cycle of water -based zinc ion batteries, ensure the stability of the charging and discharge process, maintain a good sedimentary/peeling efficiency, inhibit the growth of zinc branches, and show excellent performance under different current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381410A_ABST
    Figure CN119381410A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a water-based zinc ion battery negative electrode modified by a super-hydrophobic corrosion-resistant coating. The super-hydrophobic corrosion-resistant coating is formed by mixing a hydrophobic nano silicon dioxide dispersion liquid and an inorganic aluminum phosphate binder aqueous solution, spraying the mixture on a zinc foil and calcining. The coating can effectively isolate the contact between a solvent water in an aqueous electrolyte and a zinc negative electrode plate in the working process of the battery, so that the shelving cycle life of the aqueous zinc ion battery is prolonged, the good and stable charge and discharge process of the aqueous zinc ion battery is ensured, meanwhile, good deposition / stripping efficiency is kept, the performance is excellent under different current densities, and the service life of the aqueous zinc ion battery is prolonged. The obvious inhibition effect on zinc dendrites is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aqueous zinc ion batteries, and in particular to a method for preparing an aqueous zinc ion battery negative electrode modified with a super-hydrophobic anti-corrosion coating. Background Art

[0002] Although high energy density lithium-ion batteries (LIBs) have occupied the commercial rechargeable battery market, the limited lithium resources, high cost, and unsafe large-scale organic electrolytes have become increasingly prominent, limiting their further development. The theoretical specific capacity of the metal zinc anode is relatively high, and its mass specific capacity can reach 820mAh g -1 , with a relatively low redox potential (–0.76V relative to the standard hydrogen electrode) and strong corrosion resistance, it is one of the few metal battery systems that can use both aqueous and non-aqueous electrolytes. In addition, AZIBs batteries can be assembled in the air, greatly reducing manufacturing costs. The safety and environmental protection characteristics make aqueous zinc-ion batteries more suitable for large-scale energy storage technology applications.

[0003] However, zinc faces the challenge of low redox potential when used in aqueous zinc-ion batteries, which triggers reactions with free water molecules, produces a local alkaline environment, and causes the formation of unfavorable byproducts on the zinc surface. The uneven deposition of these byproducts leads to electric field imbalance, which in turn promotes uneven deposition of zinc ions and dendrite growth, causing membrane penetration and internal short circuits. In addition, the hydrogen evolution reaction (HER) of zinc with the electrolyte may cause battery expansion, while the accumulation of byproducts hinders ion transport in long-term operation, thereby reducing the Coulombic efficiency (CE) and hindering normal battery cycling, which seriously limits the industrial application of aqueous zinc-ion batteries.

[0004] To address these issues, researchers have proposed and implemented a variety of strategies, including designing and constructing functional interfacial layers to improve the stability of zinc anodes. For example, inorganic non-metallic coatings and organic polymer coatings can regulate and optimize the deposition mode of zinc to achieve more uniform metal deposition. Compared with organic coatings, inorganic non-metallic materials are generally more environmentally friendly and do not produce harmful volatile substances. However, most inorganic non-metallic materials have poor ion conductivity, which may cause the ion conduction channel of the zinc anode to be blocked, affecting the power performance and cycle stability of the battery. Although the interface modification technology shows good protection effect, the construction process of the SEI layer is complicated, costly and potentially unfriendly to the environment. These issues still need to be further explored. More importantly, in terms of the shelf life of the battery, the existing technology has not been able to effectively solve the problem of performance degradation caused by long-term storage, which prevents zinc-ion batteries from meeting long-term commercial storage needs.

[0005] Therefore, there is an urgent need to develop a coating material that is low-cost, easy to operate, environmentally friendly and has the ability to protect the electrochemical properties of the electrode, especially a material that can maintain excellent electrochemical properties under long-term storage conditions. Summary of the invention

[0006] The present invention provides an aqueous zinc ion battery negative electrode modified with a super-hydrophobic anti-corrosion coating and a preparation method thereof. The super-hydrophobic anti-corrosion coating effectively isolates the contact between free water in an electrolyte and a zinc electrode sheet, thereby improving the shelf cycle life of the aqueous zinc ion battery and ensuring that the aqueous zinc ion battery has a good and stable charge and discharge process, and maintains a good deposition / stripping efficiency, has excellent performance under different current densities, and has a significant inhibitory effect on zinc dendrites.

[0007] The present invention solves the above technical problems as follows: a super-hydrophobic anti-corrosion coating modified aqueous zinc ion battery negative electrode, comprising a zinc negative electrode sheet and a super-hydrophobic anti-corrosion coating modified on the surface of the zinc negative electrode sheet; the super-hydrophobic anti-corrosion coating has a thickness of 2 to 3 μm. The coating with a thickness in this range has the advantage of achieving long-term super-hydrophobic performance without affecting ion transmission.

[0008] The raw materials of the super hydrophobic anti-corrosion coating are composed of hydrophobic nano-silica and inorganic aluminum phosphate binder, and the mass ratio of inorganic aluminum phosphate binder to hydrophobic nano-silica is 1:0.2-0.8; further preferably, the mass ratio of inorganic aluminum phosphate binder to hydrophobic nano-silica is 1:0.5-0.8. The ratio of hydrophobic nano-silica and aluminum phosphate binder is precisely controlled to ensure that the coating has a considerable bonding force with the zinc negative electrode sheet and maintains long-term stable super hydrophobic properties.

[0009] Preferably, the raw materials of the inorganic aluminum phosphate binder are composed of aluminum hydroxide and 60% phosphoric acid solution, wherein the molar ratio of aluminum hydroxide to phosphoric acid is 1:3. The preparation method of the aluminum phosphate binder is as follows: phosphoric acid and aluminum hydroxide are mixed according to the ratio, and stirred at 100° C. for 3 hours to obtain the inorganic aluminum phosphate binder.

[0010] The method for preparing the negative electrode of an aqueous zinc ion battery modified with a super-hydrophobic anti-corrosion coating as described above comprises the following steps:

[0011] 1) grinding and cleaning the zinc foil to obtain a zinc negative electrode sheet;

[0012] 2) Weighing an inorganic aluminum phosphate binder and hydrophobic nano-silica respectively, and then dissolving the inorganic aluminum phosphate binder and the hydrophobic nano-silica in water and an ethanol solution respectively and mixing them evenly to obtain an inorganic aluminum phosphate binder dilution solution and a hydrophobic nano-silica dispersion solution respectively;

[0013] 3) mixing the inorganic aluminum phosphate binder dilution liquid with the hydrophobic nano-silicon dioxide dispersion liquid to obtain a super-phobic solution;

[0014] 4) Spraying the super-hydrophobic aqueous solution on the zinc negative electrode sheet and calcining the zinc negative electrode sheet to form a super-hydrophobic anti-corrosion coating on the surface of the zinc negative electrode sheet, thereby obtaining the negative electrode of the aqueous zinc ion battery.

[0015] Preferably, in step 2), the mass ratio of the inorganic aluminum phosphate binder to the hydrophobic nano-silica is 1:0.2-0.8; wherein the inorganic aluminum phosphate binder is obtained by heating and stirring aluminum hydroxide and 60% by mass phosphoric acid at a temperature of 100°C; and the molar ratio of aluminum hydroxide to phosphoric acid is 1:3.

[0016] Preferably, in step 2), the mass ratio of the inorganic aluminum phosphate binder to the hydrophobic nano-silica is 1:0.5.

[0017] Preferably, in step 2), the concentration of the inorganic aluminum phosphate binder dilution liquid is 0.2-0.4 g / mL; and the concentration of the hydrophobic nano-silicon dioxide dispersion liquid is 0.006-0.023 g / mL.

[0018] More preferably, the concentration of the inorganic aluminum phosphate binder dilution liquid is 0.2 g / mL; and the concentration of the hydrophobic nano-silica dispersion liquid is 0.014 g / mL.

[0019] Preferably, in step 4), during the spraying process, the distance between the spray gun head and the zinc negative electrode sheet is 25 cm, the spraying pressure is 40-60 Kpa, the number of spray layers is 10-15 layers, and the thickness of the super hydrophobic anti-corrosion coating is 2-3 μm.

[0020] Preferably, in step 4), the calcination includes a first stage and a second stage, wherein the first stage is drying at 120° C. for 2 hours, and the second stage is calcination at 240° C. for 1 hour.

[0021] An aqueous zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is the aqueous zinc ion battery negative electrode modified with the super-hydrophobic anti-corrosion coating as described above.

[0022] The beneficial effects of the present invention are:

[0023] (1) The preparation process of the present invention is simple, highly repeatable, has good coating effect, and the raw material safety, environmental protection and low price. The present invention adopts the method of spraying to modify the prepared super-hydrophobic solution on the zinc cathode surface, and a uniform and complete inorganic coating can be obtained, and a large area can be prepared. The super-hydrophobic surface obtained under the effect of inorganic aluminum phosphate binder can be stably present for a long time and maintain super-hydrophobic characteristics, isolating the contact of zinc metal cathode with free water in aqueous electrolyte, and effectively enhancing the corrosion resistance of zinc cathode during shelving.

[0024] (2) The inorganic aluminum phosphate binder used in the present invention has hydrophilic properties and reacts with the zinc metal surface to generate a small amount of zinc phosphate, which can regulate the zinc ion deposition (aluminum phosphate contains phosphoric acid, which reacts with zinc before calcination). At the same time, the contact between the fibers in the diaphragm and the aluminum phosphate provides a directional channel for ion transmission.

[0025] (3) The zinc negative electrode of the aqueous zinc ion battery modified with the super-hydrophobic anti-corrosion coating prepared by the present invention can effectively improve the shelf cycle life of the aqueous zinc ion battery, while ensuring that the aqueous zinc ion battery has a good and stable charge and discharge process, and maintains a good deposition / stripping efficiency, has excellent performance at different current densities, and has a significant inhibitory effect on zinc dendrites, which is helpful to realize the commercialization of aqueous zinc ion batteries.

[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 The surface morphology of Example 1 and Comparative Example 1 under a scanning electron microscope;

[0029] Figure 2 The cross-sectional morphology of Example 1 under a scanning electron microscope and the elemental analysis of an energy dispersive spectrometer;

[0030] Figure 3 is the X-ray photoelectron spectroscopy elemental analysis diagram of Example 1;

[0031] Figure 4 The wettability behavior diagram of Example 1 and Comparative Example 1 in 2M ZnSO4 electrolyte within 16 minutes;

[0032] Figure 5 The surface morphology of Example 1 and Comparative Example 1 after being immersed in 2M ZnSO4 electrolyte under a scanning electron microscope;

[0033] Figure 6 The linear sweep voltammetry curves of Example 1 and Comparative Example 1 are shown;

[0034] Figure 7 The time-current curve of the symmetrical battery composed of Example 1 and Comparative Example 1 at a voltage of -0.15V;

[0035] Figure 8 The symmetrical cells assembled in Example 1 and Comparative Example 1 were -2 Current density and 2mAh cm -2 Constant current charge and discharge data diagram of 20 cycles per 24 hours at capacity;

[0036] Fig. 9 The rate performance diagram of the symmetrical battery assembled in Example 1 and Comparative Example 1;

[0037] Fig.10 Symmetrical cells assembled for Examples 1-4 and Comparative Examples 1-2 at 5 mA cm -2 Current density and 5mAh cm -2 Constant current charge and discharge cycle data diagram under capacity;

[0038] Fig.11 The zinc negative electrode of Example 1 and Comparative Example 1 is 5 mA cm -2 Current density and 5mAh cm -2 Scanning electron microscope image of the surface after constant current charge and discharge cycles at capacity;

[0039] Fig.12 This is a long cycle performance diagram of the full battery assembled in Example 1 and Comparative Example 1 at a 5C rate after being stored for 30 days;

[0040] Fig.13 This is a rate performance diagram of the full battery assembled in Example 1 and Comparative Example 1 after being left for 7 days;

[0041] Fig.14 This is a scanning electron microscope image of the zinc negative electrode surface of the soft-pack full battery assembled in Example 1 and Comparative Example 1 after cycling. DETAILED DESCRIPTION

[0042] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0043] The raw material specifications and sources used in the following examples and comparative examples are as follows:

[0044] 1. Hydrophobic nano-silica (SiO2) was purchased from Shaoxing Lijie Chemical Co., Ltd. with the product number AEROSILR202.

[0045] 2. Bacterial cellulose (BC) membrane was purchased from Guilin Qihong Technology Co., Ltd.

[0046] 3. Aluminum hydroxide (Al(OH)3) was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0047] 4. Phosphoric acid (H3PO4) was purchased from Chengdu Kelong Chemical Co., Ltd.

[0048] 5. Zinc foil was purchased from Cyber ​​Electrochemical Materials Company.

[0049] 6. The ZnSO4 electrolyte was prepared by zinc sulfate heptahydrate and deionized water. Zinc sulfate heptahydrate was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0050] Example 1

[0051] This embodiment provides a super-hydrophobic anti-corrosion coating modified aqueous zinc ion battery negative electrode, the preparation steps of which are as follows:

[0052] 1) The zinc foil was polished with 800C, 1000C, and 2000C sandpaper in turn, rinsed with 99.9% ethanol, and then wiped dry with dust-free paper to obtain a zinc negative electrode sheet.

[0053] 2) 15.6 g of aluminum hydroxide and 98 g of 60% mass concentration phosphoric acid were heated and stirred in an oil bath at 100° C. for 3 h to obtain an inorganic aluminum phosphate binder.

[0054] 3) Dissolve 1 g of inorganic aluminum phosphate adhesive in 5 mL of pure water and stir with a magnetic stirrer for 30 min to obtain an inorganic aluminum phosphate adhesive dilution solution.

[0055] 4) Disperse 0.5 g of hydrophobic nano-silica into 35 mL of 99.9% ethanol solution, and stir for 30 min using a magnetic stirrer to obtain a hydrophobic nano-silica dispersion.

[0056] 5) Pour the inorganic aluminum phosphate binder dilution into the hydrophobic nano-silica ethanol dispersion, and continue magnetic stirring for 10 minutes to obtain a super-phobic solution (mass ratio of inorganic aluminum phosphate binder: hydrophobic nano-silica = 1:0.5).

[0057] 6) Using a spraying method, in a humidified environment, a super-repellent solution is used as the spraying liquid, at a pressure of 40 to 60 kPa, the spray gun head is sprayed at a vertical distance of about 25 cm from the zinc negative electrode sheet in step 1), and 15 to 20 layers are sprayed to evenly cover the surface of the zinc foil with the hydrophobic silica particles.

[0058] 7) The zinc foil with super-hydrophobic properties sprayed evenly in step 6) is placed in a muffle furnace, first heated at 120° C. for 2 h and then calcined at 240° C. for 1 h to make the coating solid and not easy to fall off.

[0059] Example 2

[0060] This embodiment provides a super-hydrophobic anti-corrosion coating modified aqueous zinc ion battery negative electrode, the preparation steps of which are basically the same as those of Example 1, except that:

[0061] In step 4), the amount of hydrophobic nano-silica used is 0.2 g, and in the super-phobic solution obtained in step 5), the mass ratio of inorganic aluminum phosphate adhesive: hydrophobic nano-silica is 1:0.2.

[0062] Example 3

[0063] This embodiment provides a negative electrode for an aqueous zinc ion battery modified with a super-hydrophobic anti-corrosion coating, and the preparation steps thereof are substantially the same as those of Embodiment 1, except that:

[0064] In step 4), the amount of hydrophobic nano-silica used is 0.8 g, and in the super-phobic solution obtained in step 5), the mass ratio of inorganic aluminum phosphate adhesive: hydrophobic nano-silica is 1:0.8.

[0065] Example 4

[0066] This embodiment provides a negative electrode for an aqueous zinc ion battery modified with a super-hydrophobic anti-corrosion coating, and the preparation steps thereof are substantially the same as those of Embodiment 1, except that:

[0067] In step 3), the amount of inorganic aluminum phosphate binder is 2 g, and in the superphobic solution obtained in step 5), the mass ratio of inorganic aluminum phosphate binder: hydrophobic nano-silica is 1:0.25.

[0068] Comparative Example 1

[0069] In this comparative example, a polished untreated zinc foil is used as the negative electrode of the battery.

[0070] Comparative Example 2

[0071] This embodiment provides a super-hydrophobic coating modified aqueous zinc ion battery negative electrode, and its preparation steps are basically the same as those in Example 1, except that polyvinylidene fluoride (PVDF) binder replaces inorganic aluminum phosphate binder.

[0072] The above examples and comparative examples were tested for morphology, structure, electrochemical performance and cycle rate performance of assembled batteries:

[0073] 1. Surface morphology and structural element analysis of aqueous zinc-ion battery anode modified with superhydrophobic anti-corrosion coating

[0074] like Figure 1-2 As shown in the figure, a super hydrophobic anti-corrosion coating with basically uniform thickness and no cracks is formed on the zinc foil, indicating that the super hydrophobic anti-corrosion coating is uniform and dense, and can be used to modify electrodes with different morphologies. It can be seen that the coating thickness is only 2 to 3 μm. From the EDS spectrum and Figure 3 Energy spectrum elemental analysis showed silicon, oxygen and phosphorus elements, indicating that the superphobic solution was successfully modified on the surface of the zinc foil.

[0075] 2. Anti-corrosion performance test of aqueous zinc-ion battery negative electrode modified with superhydrophobic anti-corrosion coating

[0076] like Figure 4 As shown, in the range of 0 to 16 minutes, the zinc negative electrode sheet modified by the super hydrophobic anti-corrosion coating in Example 1 always maintains a hydrophobic angle greater than 150 degrees, while the wettability of the unmodified zinc foil is getting better and better. Figure 5 As shown, the zinc negative electrode sheet modified with the super-hydrophobic anti-corrosion coating prepared in Example 1, the zinc foil modified with the super-hydrophobic anti-corrosion coating still maintained the coating integrity until the 30th day and no obvious by-products were produced; while the zinc sheet in Comparative Example 1 was immersed in 2MZnSO4 and began to produce by-products from the 5th day, and the by-products became larger and more numerous as time went on.

[0077] like Figure 6 As shown, the three-electrode method was used, with a silver chloride reference electrode and a 1M Na2SO4 solution as the electrolyte, and the HER activity on the zinc negative electrode sheet modified with the super-hydrophobic anti-corrosion coating prepared in Example 1 and the unmodified zinc negative electrode in Comparative Example 1 was tested by linear sweep voltammetry. Compared with -1.8V of the unmodified zinc negative electrode, the hydrogen evolution overpotential of the zinc negative electrode modified with the super-hydrophobic anti-corrosion coating was -1.87V, and the results showed that the zinc negative electrode modified with the super-hydrophobic anti-corrosion coating prepared in Example 1 had stronger corrosion resistance.

[0078] 3. Assembled symmetrical battery and its performance study

[0079] The stainless steel spring piece is placed in the negative electrode shell, followed by the stainless steel gasket, and then the zinc negative electrode sheet modified with the super-hydrophobic anti-corrosion coating prepared in Example 1 is placed, and then the BC diaphragm that has been cleaned, freeze-dried and soaked in 2M ZnSO4 for 12 hours is placed, and then a piece of zinc negative electrode modified with the super-hydrophobic anti-corrosion coating prepared in Example 1 is placed, and both zinc sheets are coated facing the diaphragm, and finally the positive electrode shell is covered and pressure-packaged using a press to obtain an aqueous zinc ion symmetrical battery.

[0080] The negative electrode sheets provided in Examples 2-4 and Comparative Examples 1 and 2 are assembled in the same manner as above in aqueous zinc ion symmetric batteries.

[0081] Specifically, the electrochemical performance was tested and the chronoamperometric test (CA) was performed at a voltage of -0.15 V. Figure 7 As shown, the Zn anode in the zinc negative electrode symmetric cell without surface modification in Comparative Example 1 exhibits a rapid two-dimensional diffusion process, and the rapid increase in current (absolute value) lasts for more than 500 seconds, indicating that the specific surface area rapidly expands due to the uncontrolled growth of the porous Zn deposition layer. The zinc negative electrode symmetric cell modified with a superhydrophobic anti-corrosion coating prepared in Example 1 achieves three-dimensional stable diffusion in 200 seconds, indicating that the Zn core slowly evolves to form a uniform Zn layer.

[0082] like Figure 8 As shown in the shelf cycle test of the two symmetrical batteries, each cycle was set to 20 cycles and 24 hours, and the current density was 2 mA cm -2 The capacity is 2 mAh cm -2 The zinc negative electrode symmetric battery modified with the super-hydrophobic anti-corrosion coating prepared in Example 1 can be stably cycled for more than 16 times, while the zinc negative electrode symmetric battery without surface modification in Comparative Example 1 can only be cycled 5 times.

[0083] like Fig. 9 As shown, the capacity is set to 1 mAh cm -2 , at 1~10mA cm -2 Under the current density, the polarization of the zinc negative electrode symmetric battery modified with the super hydrophobic anti-corrosion coating prepared in Example 1 is smaller and the cycle is stable. Finally, at a capacity density of 1 mAh cm -2 , current density 1mA cm -2 The cycle lasted for more than 2500 hours, and the battery had excellent rate performance. This indicates that the zinc negative electrode interface modified by the super hydrophobic anti-corrosion coating prepared in Example 1 is more stable, and the coating can reduce the generation of by-products and dendrites.

[0084] like Fig.10 As shown, the current density is set to 5 mA cm -2 The capacity is 5 mAh cm -2 As a result, in the cycling process, the voltage of Examples 2-4 and Comparative Examples 1 and 2 fluctuated greatly with the cycling time, especially the polarization fluctuation of Comparative Example 1 was huge, and finally short-circuited. However, the zinc negative electrode symmetrical battery modified with the super-hydrophobic anti-corrosion coating prepared in Example 1 can be cycled stably for more than 900 hours with lower polarization.

[0085] To further confirm the cause of battery damage, the zinc negative electrode symmetrical batteries of Example 1 and Comparative Example 1 that were tested were disassembled with pliers, the cycled zinc negative electrodes were taken out, the surface electrolyte was rinsed and removed, and their morphology was observed using a scanning electron microscope. Fig.11As shown, the surface coating of the zinc negative electrode modified by the super-hydrophobic anti-corrosion coating prepared in Example 1 is still intact and smooth without obvious by-products and dendrites. The surface of the zinc negative electrode without surface modification in Comparative Example 1 is covered with dendrites and by-products. During the cycle, the dendrites pierce the diaphragm due to the continuous accumulation of the "tip effect", causing the battery to short-circuit. This proves that the zinc negative electrode modified by the super-hydrophobic anti-corrosion coating can effectively isolate the direct contact between free water and zinc metal to achieve corrosion resistance, inhibit the generation of zinc dendrites, and thus improve the cycle life of the aqueous zinc ion battery.

[0086] 4. Assembling the full battery and its performance study

[0087] The iodine positive electrode was used as the positive electrode of the whole battery, the aqueous zinc ion battery negative electrode modified with the super hydrophobic anti-corrosion coating prepared in Example 1 was used as the negative electrode, and a BC separator and 2M ZnSO4 electrolyte were used to assemble the whole battery.

[0088] The negative electrode sheet provided in Comparative Example 1 is assembled in the same manner as above in an aqueous zinc ion symmetric battery.

[0089] The surface capacity of iodine cathode material is 0.7 mAh cm -2 The cut-off voltage of the test was about 0.3-1.6V, the test temperature was 25°C, and the button battery was installed and placed for 30 days before cycling at a current density of 5C. Fig.12 The reversible capacity of the zinc negative electrode full battery modified with the super-hydrophobic anti-corrosion coating prepared in Example 1 was cycled for more than 1000 times, and the specific capacity was still maintained at 180 mAh g -1 However, the zinc negative electrode full battery in comparative example 1 without surface modification could not be charged and discharged normally after only more than 420 cycles.

[0090] like Fig.13 As shown in the figure, at a current density of 0.1-5C, at the same cycle current density, the zinc negative electrode full battery modified with the superhydrophobic anti-corrosion coating is generally higher than the zinc negative electrode full battery without surface modification in Comparative Example 1. And when the current returns to 0.5C, the zinc negative electrode full battery modified with the superhydrophobic anti-corrosion coating shows 163mAh cm -2 The high specific capacity of the battery shows excellent cycle reversibility and rate performance. This is because the modification of the superhydrophobic anti-corrosion coating effectively blocks the contact between zinc metal and electrolyte during long-term storage of the battery, reduces the occurrence of interfacial side reactions, and leaves the ion transport channel unaffected during storage. The presence of the coating does not affect the ion insertion / extraction behavior.

[0091] 5. Assembling soft-pack full batteries and their performance research

[0092] In order to explore the practical application of the zinc negative electrode modified with super hydrophobic anti-corrosion coating, a 4cm*4cm soft-pack battery was assembled, with an iodine positive electrode block as the positive electrode, a BC separator, and a 2M ZnSO4 electrolyte. The zinc sheet prepared in Example 1 was repeated with steps 6) and 7) to prepare a double-sided super hydrophobic anti-corrosion coating-modified zinc negative electrode as the negative electrode of the soft-pack battery, and finally assembled using the equipment for assembling soft-pack batteries. The above negative electrode was replaced with the zinc negative electrode of Comparative Example 1, and the soft-pack battery was assembled with the same materials.

[0093] After the assembled soft-pack battery was set aside for 10 days and cycled 40 times at a current density of 0.5C, the battery was disassembled, the zinc negative electrode after the cycle was taken out for cleaning and drying, and the surface was observed by scanning electron microscopy. Fig.14 As shown, the surface of the zinc negative electrode modified with the super hydrophobic anti-corrosion coating prepared in Example 1 is very flat, with little byproduct and dendrite generation, while the surface of the zinc negative electrode of Comparative Example 1 has obvious byproduct and dendrite generation. This is because the zinc negative electrode modified with the super hydrophobic anti-corrosion coating in Example 1 can effectively reduce the occurrence of interfacial side reactions, reduce corrosion and inhibit dendrite growth, so that the aqueous zinc ion battery still exhibits excellent cycle stability and rate performance even after being shelved for a long time.

[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A super-hydrophobic anti-corrosion coating modified aqueous zinc ion battery negative electrode, characterized in that, It comprises a zinc negative electrode sheet and a super hydrophobic anti-corrosion coating modified on the surface of the zinc negative electrode sheet; the thickness of the super hydrophobic anti-corrosion coating is 2 to 3 μm.

2. A super-hydrophobic anti-corrosion coating modified aqueous zinc ion battery negative electrode according to claim 1, characterized in that, The raw materials of the super hydrophobic anti-corrosion coating consist of hydrophobic nano-silica and inorganic aluminum phosphate binder, and the mass ratio of the inorganic aluminum phosphate binder to the hydrophobic nano-silica is 1:0.2-0.

8.

3. A kind of aqueous zinc ion battery negative electrode modified by super hydrophobic anti-corrosion coating according to claim 3, characterized in that, The mass ratio of the inorganic aluminum phosphate binder to the hydrophobic nano-silica is 1:0.

5.

4. A super-hydrophobic anti-corrosion coating modified aqueous zinc ion battery negative electrode according to claim 1, characterized in that, The raw materials of the inorganic aluminum phosphate binder are composed of aluminum hydroxide and phosphoric acid with a mass concentration of 60%, wherein the molar ratio of aluminum hydroxide to phosphoric acid is 1:

3.

5. A method for preparing an aqueous zinc ion battery negative electrode modified with a super-hydrophobic anti-corrosion coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) grinding and cleaning the zinc foil to obtain a zinc negative electrode sheet; 2) Weighing an inorganic aluminum phosphate binder and hydrophobic nano-silica respectively, and then dissolving the inorganic aluminum phosphate binder and the hydrophobic nano-silica in water and an ethanol solution respectively and mixing them evenly to obtain an inorganic aluminum phosphate binder dilution solution and a hydrophobic nano-silica dispersion solution respectively; 3) mixing the inorganic aluminum phosphate binder dilution liquid with the hydrophobic nano-silicon dioxide dispersion liquid to obtain a super-phobic solution; 4) Spraying the super-hydrophobic aqueous solution on the zinc negative electrode sheet and calcining the zinc negative electrode sheet to form a super-hydrophobic anti-corrosion coating on the surface of the zinc negative electrode sheet, thereby obtaining the negative electrode of the aqueous zinc ion battery.

6. according to claim 5 a kind of preparation method of the aqueous zinc ion battery negative electrode modified by super hydrophobic anti-corrosion coating, it is characterized in that, In the step 2), the mass ratio of the inorganic aluminum phosphate binder to the hydrophobic nano-silica is 1:0.2-0.8; wherein the inorganic aluminum phosphate binder is obtained by heating and stirring aluminum hydroxide and 60% by mass phosphoric acid at a temperature of 100° C.; and the molar ratio of aluminum hydroxide to phosphoric acid is 1:

3.

7. according to claim 5 a kind of preparation method of the aqueous zinc ion battery negative electrode modified by super hydrophobic anti-corrosion coating, it is characterized in that, In the step 3), the concentration of the inorganic aluminum phosphate binder dilution liquid is 0.2-0.4 g / mL; the concentration of the hydrophobic nano-silicon dioxide dispersion liquid is 0.006-0.023 g / mL.

8. according to claim 5 a kind of preparation method of the aqueous zinc ion battery negative electrode modified by super hydrophobic anti-corrosion coating, it is characterized in that, In the step 4), the spraying pressure is 40-60 Kpa, the number of spray layers is 10-15 layers, and the total thickness of the super hydrophobic anti-corrosion coating is 2-3 μm.

9. according to claim 5 a kind of preparation method of the aqueous zinc ion battery negative electrode modified by super hydrophobic anti-corrosion coating, it is characterized in that, The step 4) calcination includes a first stage and a second stage; wherein the first stage: drying at a temperature of 120° C. for 2 hours, and the second stage: calcination at a temperature of 240° C. for 1 hour.

10. An aqueous zinc ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The negative electrode is an aqueous zinc ion battery negative electrode modified with the super-hydrophobic anti-corrosion coating according to any one of claims 1 to 4.